Gordonia terrae kidney graft abscess in a renal transplant patient. Issue 4 (26th June 2014) - Nicodemo, A.C.; Odongo, F.C.A.; Doi, A.M.; Sampaio, J.L.M.
Abstract We present the first report, to our knowledge, of a renal abscess cause by an infection from Gordonia terrae in a kidney transplant patient. The patient simultaneously had pulmonary tuberculosis and a perirenal allograft abscess caused by G. terrae. After treatment with imipenem, in addition to anti‐tuberculous drugs, the patient was cured.